Brain injuries in American football: understanding the injury, difficulty in helmet optimization, and current communication practices - a narrative review - Sebastian, K. M.; Burch V, R. F.; Rogers, P. (International Journal of Kinesiology & Sports Science, 2020)
Background: Over 2.7 million people suffer traumatic brain injuries (TBIs) annually in the United States. TBI involves the application and generation of external forces and impulse loads respectively to the head whereby the brain moves relative to the skull. Despite numerous studies, further understanding of TBIs is necessary, requiring consistent attention. Objective: The purpose of this article is to investigate the history of American football helmets and provide an academic and practitioner review as it relates to TBIs. This study is a literature review that also considers perspectives from an autoethnographic frame. Method: An extensive literature review was performed to assess the history of TBI as it relates to American football. This article evaluates helmet design optimization and American football safety as well as an exploration into the sports` education methods for players and staff alike. Results: Despite developing helmet designs that can better attenuate impact forces, reducing linear and rotational movement, the skull and brain move very differently relative to one another. Helmet designs and tools for measuring forces require further validation techniques to determine resultant forces and movement for the brain. Current biomechanics research lacks sufficient methodology for defining TBI thresholds, making helmet optimization difficult. Conclusion: According to past research, no helmet can eliminate all TBI risk; however, processes are in place lead by the National Football League (NFL) and NFL Players Association to educate players, coaches, and staff at all levels of competition of the protective capabilities of available helmet options.